Wages, compositional effects and the business cycle - Styliani Christodoulopoulou; Omiros Kouvavas (European Central Bank (ECB), 2022)
During the Great Recession, unemployment increased substantially across several euro area countries, with wages exhibiting a muted response. As low skilled workers lose their jobs first during a recession, the remaining employed workers result in a relatively more skilled employment pool. This change in the composition of the employed workers in ates the aggregate wage mechanically, even in the case of no actual pay rises. This paper uses individual level data to control for the effect of changes in the composition of workers on wages and wage cyclicality. We find that compositional effects are highly correlated with the severity of the business cycle, being significant in countries where employment losses were larger. Thus, the results partially explain the muted response of the observed wages to the business cycle, as wages decreased more than what the aggregate numbers suggest during the downturn, a picture that is reversed somewhat during the recent recovery.
Keywords: J30; E32; 330; Wages; Compositional e ects; Wage cyclicality